PENGEMBANGAN MODUL PELATIHAN KEPEMIMPINAN GURU WALI KELAS UNTUK PENINGKATAN KEDISIPLINAN DAN BIMBINGAN KARIER SISWA - Marsidik Marsidik; Muhammad Sayuti; Tri Kuat (Jurnal Pendidikan Ilmu Sosial, 2022)
This research aims to analyze the training modules currently in use, develop homeroom teacher leadership training modules that meet the valid, practical and effective criteria, and analyze the validity, practicality and effectiveness of the modules. This research uses research and development (RD) methods, the product developed is a homeroom teacher leadership training module. The development steps use a modified RD step, namely preliminary studies, development, and testing. Data collection techniques using documentary studies, observations and interviews. The data analysis technique used qualitative and quantitative approaches. The subjects of this study were homeroom teachers at SMK Negeri 3 Kasihan. The results achieved in this study were the homeroom teacher leadership training module which was developed based on the analysis of the principal strengthening training module. The developed module meets the valid criteria based on the validation test of material experts and learning experts with an average value of 71%. The results of the assessment analysis of the module trial participants showed that the module met the practical criteria with an average score of 96%, then based on data analysis using the t-test showed that the value of Sig. (2-tailed) which is .000 less than 0.05 interpretation, there is a significant difference in effectiveness between the experimental class and the control class, it can be concluded, this homeroom teacher leadership training module is effectively applied in homeroom teacher leadership training.